SOIL CARBON DYNAMICS AND PHYSICAL CHARACTERISTICS IN DIFFERENT COFFEE AGROECOSYSTEMS - Nur Ulina Warnisyah Sebayang; Putri Chandra Ayu; Rahmawaty; Sendi Puspa Sari; Mohd Hasmadi Ismail (Jurnal Belantara, 2026)
Coffee management systems strongly influence soil carbon dynamics and soil physical quality in tropical agroecosystems. This study aimed to evaluate soil carbon dynamics and selected soil physical characteristics under organic (ORG), semi-organic (SEM), and conventional (CON) coffee management systems at soil depths of 0–10, 10–20, 20–30, and 30–40 cm. Observed parameters included total organic carbon (TOC), carbon sequestration, bulk density, and aggregate stability. The results showed that ORG consistently exhibited the highest TOC values, particularly at the 0–10 cm depth (3.21%), followed by SEM (2.74%) and CON (2.18%). Soil carbon sequestration under ORG was approximately 24% greater than CON, indicating improved carbon storage potential under continuous organic matter inputs. Aggregate stability was also higher under ORG across all aggregate size fractions, especially within the 63 µm fraction, while CON exhibited lower aggregate stability and greater bulk density, indicating higher soil compaction. TOC values gradually decreased with increasing soil depth across all management systems, reflecting reduced organic matter inputs in subsurface soils. Overall, organic coffee management with continuous organic amendments and minimal soil disturbance improved soil carbon storage and enhanced soil physical quality.